2x-(x-1)=5(x-3)

Simple and best practice solution for 2x-(x-1)=5(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x-(x-1)=5(x-3) equation:


Simplifying
2x + -1(x + -1) = 5(x + -3)

Reorder the terms:
2x + -1(-1 + x) = 5(x + -3)
2x + (-1 * -1 + x * -1) = 5(x + -3)
2x + (1 + -1x) = 5(x + -3)

Reorder the terms:
1 + 2x + -1x = 5(x + -3)

Combine like terms: 2x + -1x = 1x
1 + 1x = 5(x + -3)

Reorder the terms:
1 + 1x = 5(-3 + x)
1 + 1x = (-3 * 5 + x * 5)
1 + 1x = (-15 + 5x)

Solving
1 + 1x = -15 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
1 + 1x + -5x = -15 + 5x + -5x

Combine like terms: 1x + -5x = -4x
1 + -4x = -15 + 5x + -5x

Combine like terms: 5x + -5x = 0
1 + -4x = -15 + 0
1 + -4x = -15

Add '-1' to each side of the equation.
1 + -1 + -4x = -15 + -1

Combine like terms: 1 + -1 = 0
0 + -4x = -15 + -1
-4x = -15 + -1

Combine like terms: -15 + -1 = -16
-4x = -16

Divide each side by '-4'.
x = 4

Simplifying
x = 4

See similar equations:

| 42x^2-5x-3=0 | | -20=2(w+7)-4w | | t/25=14/10 | | -9x-73=67-14x | | 4x+26x-9=6(5x+5) | | 3x-6=40 | | 3x-6+2x-4=30 | | 5x-40=8x+11 | | 28-4x=13-9x | | -161+8x=2x+99 | | 12x+15=5x+7 | | (x-1)+(x-1)=g | | y-2=(22-y)^(1/2) | | -114-2x=210+7x | | (x^2)-2x-2.5=0 | | 3a-27=54+9a | | 3x-22=13+4x | | -14+10x=11x+13 | | 5(x-2)=80-5x | | 5x-3=67-9x | | g(x)=-log^2(x-3)+1 | | -91+3x=-x+37 | | g(x)=-log^2(x-3) | | 8x+1=7-20 | | 2/3(15)=10 | | -(X^2-8X-9)=0 | | 7x+9=x+11 | | 5/y-3/4 | | Y=-14x^2+84x | | 3x-32=-2 | | 3(x-4)=-24 | | log(3x+2)=2.27 |

Equations solver categories